Perceraian dalam Perspektif Psikologi Pendidikan Islam - Hadiwijaya, Lalu Firman; Sutrisno, Agus; Rokhimatun, Siti (TSAQOFAH, 2025)
Divorce is a social and psychological event that significantly impacts child development, particularly in terms of morality, emotional well-being, and academic performance. From an Islamic perspective, divorce is permitted as a last resort after all forms of mediation and reconciliation have failed. Islamic educational psychology views divorce as a serious challenge to character development, as children affected by divorce are at risk of identity crises, learning difficulties, and behavioral problems. This study aims to analyze the impact of divorce on children from the perspective of Islamic educational psychology and emphasizes the importance of a comprehensive approach based on Islamic values such as tawhid, akhlaq, patience, and tawakkul in the post-divorce parenting process. The method used is a literature review, examining relevant verses of the Qur’an, hadith, and theories of Islamic educational psychology. The findings indicate that the synergy between parents, teachers, schools, and the broader community plays a crucial role in fostering children's mental and spiritual resilience, enabling them to grow and develop optimally even in the context of a non-intact family.